Biological responses of MC3T3-E1 on calcium carbonate coatings fabricated by hydrothermal reaction on titanium. (4th March 2020) - Le Thi, Bang; Shi, Rui; Long, Bui Duc; Ramesh, S; Xingling, Shi; Sugiura, Yuki; Ishikawa, Kunio
Abstract: Titainum (Ti) implants have been successfully used in orthopaedic and dental surgery. However, poor early bone tissue integration is still a common cause of implant failure. This could be modulated by improving the material bonding or adhesion directly to the bone by surface roughening and/or a bioresorbable and osteoconductive coating. In this study, we report on the biological behaviours of the Ti substrate with modified surface roughness and/or a calcium carbonate (CaCO3 ) coating. The roughened Ti surface was prepared using an acid etching reaction, and the CaCO3 coating on the substrates was synthesized by the hydrothermal treatment of Ti in calcium citrate complexes. This study demonstrates that surface roughening of Ti alone does not improve the biological response of the MC3T3-E1 cells, but a CaCO3 coating on the smooth Ti surface increases cell responses, and these effects are further enhanced by the combination of coating a roughened Ti surface with CaCO3 . The larger the cell area, the greater the cell proliferation and increased bone-like nodule formation were observed on the CaCO3 coating of the roughened Ti surface. This observation was also supported by a higher ALP value. The cell behaviours found in the current study further support the development of CaCO3 coatings towards clinical application.